Adaptation, Translation and Validation of The Warwick-Edinburgh Mental Well-Being Acreda Scale (WEMWBS-ACREDA) - Amin Al Haadi Shafie; Mohd Rushdan Mohd Jailani; Mohamad Isa Amat; Khairunneezam Mohd Noor; Abd Halim Bin Mohd Husin; Adam Fariz; Mohd Rafidi Bin Jusoh (IDOSI Publications, 2024)
The Warwick-Edinburgh Mental Well-Being Scale (WEMWBS) was developed to assess the mental well-being of an individual or population. This study reports the processes of translation, validation and analysis of the reliability of the Malay version of the WEMWBS (WEMWBS-ACREDA). The instrument consists of 20 positively worded items and uses a5-point likert scale. The 14 original items in the WEMWBS were maintained and 6 new items measuring spirituality were added. The adaptation, translation and validation processes for the instrument were performed by four experts in counselling and psychology with Malay and English language competency. The experts used face validity and back translation techniques. A pilot test was conducted to determine the reliability of the new translated version of the WEMWBS-ACREDA and involved 51 randomly selected in-patients at the Cure and Care Clinic. The data were analysed using Cronbach's alpha and the result of 0.91 indicated high reliability. These findings indicate that the translated version of the WEMWBS-ACREDA is reliable and appropriately measures the mental well-being of normal individuals involved in drug abuse in a local setting. Moreover, the new translated version of the WEMWBSACREDA represents a short and convenient psychological tool. However, further studies are recommended to support the findings of this research.